Black notice - Cornwell, Patricia Daniels (New York : G.P. Putnam's Sons, 1999)
Evidence uncovered in an investigation of a decomposed body found on a freighter leads medical examiner Kay Scarpetta to Interpol's headquarters in France.
730
Accelerated Reader AR
Keywords: Scarpetta, Kay (Fictitious character) -- Fiction; Mystery fiction